Sentralistik Kekuasaan di Nagori Tiga Ras Periode 2008-2015 - NOVELLI GIRSANG (Politeia: Jurnal Ilmu Politik, 2016)
This study tries to observehow the political relations between Panguluas an executive agency-with Maujana Nagorias a legislative agency at the level of Nagori. Precisely political relation of pangulu and Maujana in Nagori Tiga Ras, Kecamatan Dolok Pardamean, Kabupaten Sima-lungun 2008-2015 Period. It focus on discussing about what thecauses of thepower centralized in Nagori Tiga Ras.The findings of the study is there are six important things tobe themain cause of power centralizedin Nagori Tiga Ras. First, the lack of human resources; Second, the-lack of Maujana Nagori’s understanding about their responsibilities; Third, the difficulty of ad-just ment to the new regulations; Forth, maujanaNagori’ssalaries is low; Fifth,the strong cul-ture of family and; Sixth, the influences feudal cultural. This research method is qualitative re-search with descriptive method, where thedescriptive researchis ameans usedtosolve theexisting problems based on facts and data available. Data collection techniques performed by the me-thod of direct interview.Keywords Political relation, Power, Centralization.